What Can Covid Teach Us? An Essay - Bussey, Marcus (International Dialogues on Education Journal, 2022)
This essay explores the broader implications for education of the Covid-19 pandemic. It asks: What can Covid teach us? The case is made that Covid is inviting us to consider a relational universe, and what a pedagogy of presence would look like. It takes a futures perspective and is therefore, unabashedly speculative. It draws on the author’s many years as both a teacher and as a university lecturer in cultural change and futures studies. The essay speaks to the pedagogical imagination as a tool for rethinking learning and our collective futures. The paper concludes that love, intimacy, and presence are very much part of educational and cultural discourses and that though currently eclipsed by a technocratic and neoliberal discourse, they are being called forth as a possible response to the Covid pandemic.